Microbial-earthworm ecofilters (MEES) for urban wastewater treatment - Ahmed Alghamdi (South African Journal of Chemical Engineering, 2023)
Water is an absolute necessity for life and water scarcity is a major problem all over the world. Reusing household wastewater for non-potable water applications is one of the solutions to tackle this problem. Many developing countries lack the technological resources to construct and operate costly wastewater treatment plants. They need cost-effective wastewater treatment options so that both economic aspects and human needs can be met easily. Centralized sewage treatment systems are unable to achieve future demands for sustainable wastewater management in developing countries due to the growing population and needs. The present work examines the effectiveness of treating urban wastewater with microbial-earthworm eco filters (MEEs) (reactor 2) and the filter unit without earthworms (reactor 1). Results of the use of the vermi-biofiltration wastewater treatment unit comprising the biological filtration treatment unit, Eisenia fetida earthworm species, live soil organisms, and natural stones to treat household wastewater are reported herein. The biological oxygen demand (BOD), total dissolved solids (TDS), chemical oxygen demand (COD), and total organic carbon (TOC) were monitored for seven weeks. These parameters exhibited a decreasing trend in both the filtration units. A 75 % reduction in TOC for reactor 2 shows the effectiveness of the proposed system for the utilization of wastewater from urban households. Reactor 2 also showed a reduction in BOD, COD, and TDS approximately in the range of 85, 90, and 30 % respectively. This technique seems to be useful for developing a low-cost and useful household purification system in water-scarce areas using harmless bio-organisms.